Hydrolysis of Solid Waste From Bioethanol Plants into Glucose Using Hydrochloric Acid Catalyst - Mochammad Rifqi Ardiansyah; Nashrul Haqqi; Sani (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The large amount of solid waste from bioethanol plants is regrettable if it is only used as animal feed. The solid waste has a relatively high carbohydrate content of 36.85%, which has the potential to be hydrolysed to glucose. Hydrolysis with water is slow, so a catalyst is needed to speed up the reaction. HCl hydrolysis is commonly used to convert carbohydrates to glucose. The hydrolysis process in this study involved heating at 95°C with a stirring speed of 300 rpm. The variables tested were hydrolysis time (90, 120, 150, 180, 210 minutes) and HCl concentration (1.5, 2, 2.5, 3, 3.5N). The results showed that hydrolysis time and HCl concentration had a direct effect on glucose yield. The longer the hydrolysis time and the higher the concentration used, the higher the glucose yield. The highest glucose content obtained was 23.12%, with a yield of 70.6%, obtained under the conditions of 210 minutes hydrolysis time and 3.5 N HCl concentration.